New mode for the on –line determination of metoclopramide hydrochloride in pure and pharmaceutical preparations via the use of homemade Ayah 6SX1-T-2D Solar cell CFI Analyser - Turkey Al-Awadie, Nagam S.; Ismael Al-saadi, Kefah H. (Iraqi Journal of Science, 2023)
A newly developed analytical method characterized by its speed and sensitivity for the determination of metoclopramide hydrochloride (MCP-HCl) in pure and pharmaceutical preparations via absorbance measurement by Ayah 6SX1-T-2D Solar cell-CFI Analyser. The method is based on the oxidation of the drug with Ce(IV)sulfate in acidic medium to form a red color species which determined using homemade Ayah 6SX1-T-2D Solar cell . Chemical and physical parameters were studied and optimized. The calibration graph was linear in the range of 0.05- 16 mMol.LP-1Pwith correlation coefficient r = 0.9855. The limit of detection(S/N = 3) 0.332 μg/sample from the step wise dilution for the minimum concentration in the linear dynamic ranged of the calibration graph. The RSD% at 2 and 6mMol.LP-1P metoclopramide hydrochloride is less than 0.6% (six replicate). The method was successfully applied for the determination of metoclopramide hydrochloride in three pharmaceutical drugs. A comparison was made between the newly developed method analysis with the classical method (UV-Vis spectrophotometry at λ max 474 nm) using the standard addition method via the use of t-test. It was noticed that there was a significant difference between two methods at 95 % confidence level.